(untitled) (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This study aims to describe the application of mindfulness therapy in managing emotions and increasing self-confidence in adolescents in orphanages. The research method in this study uses qualitative research methods. Where in this study the researcher took one of the teenage informants at one of the orphanages in Medan City, namely at LKSA Naungan Kasih Kemuliaan. The characteristics of adolescents who become informants are adolescents who experience mental emotional disorders. To make it easier for researchers to carry out effective and efficient interventions, researchers use a casework method approach in social work with BPSS (Bio Psychology Social Spiritual) tools or tools that include biological, psychological, social, and spiritual related which will be a guide in assessing informants. These two methods are used by researchers to obtain accurate results that will be able to determine the success of the intervention stage that will be carried out together with the informant. The results of this study revealed that there were changes in the informants in a more positive direction with the application of mindfulness therapy that had been undertaken for approximately two months. This shows that the application of mindfulness therapy is quite effective in overcoming mental emotional disorders of adolescents, especially adolescents who are in orphanages, especially related to emotional management and increasing self-confidence.